The differences of Semantics of Common Words between Arabic and Urdu and its Impact on the teaching of the Arabic language - Ahmed, Zahir (Journal of Islamic and Religious Studies, 2017)
Arabic language is a family member of Semitic languages whereas Urdu is the member of Indo-European Languages. The Arabic language though is not from the same language family but amazingly it provides much of its share through alphabets, words with its meanings and pronunciation. These features of both languages have provoked to study it under the contrastive linguistics through semantic study of commonly used words. This research is a semantic study of commonly used words in both languages of different language family along with the applied linguistics in Language teaching. There are large numbers of Arabic words that are used in Urdu language and there are significant numbers of words that are used in different meanings, this change in meaning led to change in semantic field. This research paper also study the effect of semantic change of these words on Arabic Language teaching to the Pakistani students whose native language is Urdu. This study will also reveal the reasons of errors during language learning with the help of semantic study if commonly used words.